Сontinual Interaction of Personal Safety and Psychoemotional Burnout of a Person: Theoretical Aspects - Bretsko, Irina; Finiv, Olga (Psychological Prospects Journal, 2018)
The article reveals psychological peculiarities of interaction of personal safety and psychoemotional burnout of a person. The theoretical analysis of the studied phenomena has been carried out, the continual character of the relationships between the experiences of personal safety and affective disorders, the most common of which is psychoemotional and psychophysical exhaustion has been established. It has been established that numerous threats of a natural and social nature are caused by the sensation of a large number of people of the experiences of anxiety, fear, despair, which are generally concentrated in such conceptual discourse as «the absence of personal security». It has been stated that conditions of uncertainty, dichotomy, disturbed balance essentially imbalance the personal homeostasis, affecting the neuropsychic dysfunction of the human body and manifested itself both in the psychophysical and social levels of self-realization. Feeling a threat to personal safety, a person is particularly responsive to stressors, experiencing discomfort and demonstrating behavioral dysfunctions. Possibility of psychological security, as observance of the intellectual and emotional balance between the feelings of personal security and the level of overcoming basal anxiety has been emphasized. It has been emphasized that in conditions of family deprivation, children are largely experiencing an increased level of psychoemotional burnout and affective exhaustion. This is due to the predominance of a sense of neglect, and therefore of experience as a result of this unnecessary, social outsider, personal deprivation and other depressed self-conscious attributes, in particular because of the lack of personal security. The lack of a firm feeling of personal security leads to excessive psycho-emotional exhaustion, psychophysical exhaustion, excessive psychosis, passive vital intentions and general depressive modus of self-awareness and life has been noted.